2011
DOI: 10.1038/nn.2761
|View full text |Cite
|
Sign up to set email alerts
|

Self-related neural response to tailored smoking-cessation messages predicts quitting

Abstract: Although tailored health interventions can be more effective in eliciting positive behavior change then generic interventions, the underlying neural mechanisms are not yet understood. Ninety-one smokers participated in a functional magnetic resonance imaging (fMRI) session and a tailored smoking-cessation program. We found that increases in activations in self-related processing regions, particularly dorsomedial prefrontal cortex, to tailored messages predicted quitting during a 4-month follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
192
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(215 citation statements)
references
References 12 publications
21
192
1
1
Order By: Relevance
“…Neural responses can be recorded as affirmation and subsequent persuasion occur, without requiring self-report assessments that could interfere with the message recipient's natural thought processes. In support of this idea, our team has used neural predictors to augment understanding of health behavior change in response to interventions in other domains (42)(43)(44)(45)(46)(47)(48)(49)(50).…”
Section: Self-affirmationmentioning
confidence: 99%
See 1 more Smart Citation
“…Neural responses can be recorded as affirmation and subsequent persuasion occur, without requiring self-report assessments that could interfere with the message recipient's natural thought processes. In support of this idea, our team has used neural predictors to augment understanding of health behavior change in response to interventions in other domains (42)(43)(44)(45)(46)(47)(48)(49)(50).…”
Section: Self-affirmationmentioning
confidence: 99%
“…VMPFC is the most common region implicated in self-related processing (51) and is also a key region, along with the ventral striatum, implicated in positive valuation of stimuli (52). In addition, VMPFC has been consistently associated with behavior change in response to health messages in prior work (44)(45)(46)50). This prior research has suggested that the link between VMPFC activity during health message exposure and behavior change may stem from a recipient's ability to process a health message as self-relevant or as having value to oneself.…”
Section: Potential Neural Mechanisms Of Affirmationmentioning
confidence: 99%
“…Furthermore, as described above, the team specifically localized the effects to sub-regions of MPFC implicated in self-related processing and valuation, and demonstrated that the effects were specific to activity during the PSAs and not individual differences in general reactivity within MPFC (Cooper, Tompson, O'Donnell, & Falk, in press). In addressing how these neural findings can translate to message design, as described above, MPFC activity can be increased by intervention components that increase self-related processing, such as message tailoring (Chua et al, 2011). Recent studies described above also suggest that neural data may be useful in identifying messages that are later most effective in producing population level behavior change, despite not being identified through participant self-reports (e.g., Falk et al, 2012;under review).…”
Section: Using the Brain-as-predictor Approach To Test Theories In Comentioning
confidence: 99%
“…Members of the dental profession have a unique opportunity to influence tobacco use by their patients. [27] Dentists are obligated to help patients quit because tobacco use is the most common underlying cause of periodontal and many other oral diseases and conditions, apart from the risks to quality of life and to life itself. [28]Evidence is overwhelming that tobacco damages oral health and that clinical cessation methods work in dental practice.…”
Section: Conclusion:-mentioning
confidence: 99%